Adult Asthma Consensus Guidelines Update 2003. (2004) - Lemière, Catherine; Bai, Tony; Balter, Meyer; Bayliff, Charles; Becker, Allan; Boulet, Louis-Philippe; Bowie, Dennis; Cartier, André; Cave, Andrew; Chapman, Kenneth; Cowie, Robert; Coyle, Stephen; et al.
Abstract : BACKGROUND: Several sets of Canadian guidelines for the diagnosis and management of asthma have been published over the past 15 years. Since the last revision of the 1999 Canadian Asthma Consensus Report, important new studies have highlighted the need to incorporate new information into the asthma guidelines. OBJECTIVES: To review the literature on adult asthma management published between January 2000 and June 2003; to evaluate the influence of the new evidence on the recommendations made in the 1999 Canadian Asthma Consensus Guidelines and its 2001 update; and to report new recommendations on adult asthma management. METHODS: Three specific topics for which new evidence affected the previous recommendations were selected for review: initial treatment of asthma, add-on therapies in the treatment of asthma and asthma education. The resultant reviews were discussed in June 2003 at a meeting under the auspices of the Canadian Thoracic Society, and recommendations for adult asthma management were reviewed. RESULTS: The present report emphasises the importance of the early introduction of inhaled corticosteroids in symptomatic patients with mild asthma; stresses the benefit of adding additional therapy, preferably long-acting beta2 -agonists, to patients incompletely controlled on low doses of inhaled corticosteroids; and documents the essential role of asthma education. CONCLUSION: The present report generally supports many of the previous recommendations published in the 1999 Canadian Asthma Consensus Report and provides higher levels of evidence for a number of those recommendations.